EBLUP-SMALL AREA ESTIMATION METHOD FOR PER CAPITA EXPENDITURES IN BALI - AMALIANA, LUTHFATUL; DEWI, MADE LARAS SETYANA (E-Jurnal Matematika, 2022)
Small Area Estimation (SAE) is a statistical technique for estimating the parameters of a sub-population with a small sample size. SAE aims to improve the accuracy of parameter estimation , with indirect estimation. This study aims to determine the best method between empirical best linear unbiased prediction ( EBLU P) and spatial EBLUP methods (with a queen contiguity weighted matrix) in estimating per capita expenditure per sub-district in Bali . The results of this study indicate that the best SAE method in estimating per capita expenditure per sub-district in Bali is the EBLUP method with the smaller mean squared error. The EBLUP estimation results are significantly influenced by three variables, namely the population, public primary schools, and families using PLN. The sub-district with the highest per capita expenditure in Bali is Denpasar Selatan sub-district. Meanwhile, the sub-district with the lowest per capita expenditure was Abang sub-district. Since the EBLUP model is better than SEBLUP model, this indicates that per capita expenditure per sub-district in Bali is not influenced by its neighbors.